STRUGGLE FOR LIFE, DIGNITY, AND COURAGE OF ANNABELLE WORTHINGTON IN DANIELLE STEEL’S A GOOD WOMAN : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Anggriawan, Deva Fery (LANTERN (Journal on English Language, Culture and Literature), 2013)
Novel is a part of literatur that the reader will receive knowledge from novel. A Good Woman is one of the best seller novel that establised in 2008 by Danielle Steel, published by Random House on October 2008. This research will analyze the structural elements from novel A Good Woman and analyze the struggle of life of Annabelle Worthington, her dignity and her courage through psychological approach. Based on the analysis and discussion, we can conclue that The structural elements of A Good Womannovel take setting in 1912’s, with Annabelle Worthington as the protagonist, who has a strong character, smart and remarkable woman. Annabelle Worthington has a great story of struggle for life, dignity and courage in Danielle Steel’s A Good Woman.The 'id' and the 'superego' are constantly in conflict with each other, and the 'ego' tries to resolve the discord. If this conflict is not resolved, we tend to use defense mechanisms to reduce our anxieties. Psychoanalysis attempts to help patients resolve their inner conflicts. Annabelle has ‘id’ and ‘superego’ so she involved conflict with another, especially her struggle for life and dignity. As she learn from her past and make a new life and relationship in France, she become a remarkable woman who did not tied in a marriage and can accept all the risk and take the chance in flowing the life.